An assessment of the influence of global market developments in the metal mining production of Cu, Pb and Zn, 1995-2013 - Ospino Edery, Ysaac (2017)
The present investigation, leads us to appreciate the evolution of the Legal framework in which our mining metallurgical activity has developed its initial way, between the years 1992 and the present. Likewise, a microeconomic perspective of supply and demand such as production and exports, the same ones that have a substantive increase in volumes as a result of the investments carried out after the implementation of promotional and liberal legislation, as well as by high prices registered in the market of metals of which we are part.Finally, the implication and empirical evidence of the relationship that is given between the production metal mining of the not ferrous and the evolution of the world market is considered. Understood as different manifestations of the economic cycle in the evolution of GDP facing the main demanding country economies of concentrates and refined.